EDITORIAL PAPER - MANAGEMENT - JT ADMIN (Journal of Techniques)
The Journal of Techniques is committed to publishing original practical and empirical scholarly research articles, which have high impact on the management field and its application as a whole. In addition, this Journal encourages new ideas or new perspectives on existing research that represents the entire spectrum of research on management and its application, ranging from analytical models to descriptive articles and case studies.